Assessing the Impact of Green Innovation on Corporate Sustainable Development - Liao, Yu; Qiu, Xiaodong; Wu, Anni; Sun, Qian; Shen, Haomin; Li, Peiyang (Frontiers in Energy Research, 2022)
Under the background of increasingly prominent environmental problems, exploring the impact of green innovation on the sustainable development ability of enterprises can not only expand the boundary of the research on the factors influencing enterprises' sustainable development ability and the economic consequences of green innovation, but also provide reference for the decision-making of listed companies. Based on the manual collection of green innovation patent data from China National Intellectual Property Administration, this paper selects the Chinese A-share listed companies from 2010 to 2018 as the research subject, and empirically tests the impact of green innovation on corporate sustainable development ability. The results show that the output of green innovation significantly improves corporate sustainable development ability. This result is economically significant. Specifically, a one-standard-deviation increase (0.8147) of GI translates into an SGR of 20.78 percentage points (0.0175*0.8147/0.0686) higher. The relationship between the output of green innovation and corporate sustainable development ability is more significant when corporate social responsibility performance is worse or scientific research ability is weaker. A series of robustness test results show that the conclusions are reliable. Further test shows that green innovation plays a more significant role in enhancing corporate sustainable development ability in non-state-owned enterprises. In addition, only invention patents of green innovation can significantly improve corporate sustainable development ability, while non-invention patents can’t affect it. This paper provides a new perspective for the research on the factors affecting corporate sustainable development ability. Furthermore, the research conclusions of this paper are of reference significance both in theory and practice.